Mastering micro-filamentation for semiconductor-metal ultrafast laser welding - Chambonneau, Maxime; Li, Qingfeng; Fedorov, Vladimir Yu; Blothe, Markus; Tzortzakis, Stelios; Nolte, Stefan (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Ultrafast laser welding is a proven technique which enables to bond a wide variety of materials together. This technique relies on laser energy deposition at the interface between two materials. While, to date, ultrafast laser welding has been demonstrated in numerous material configurations such as glass-glass, glass-semiconductor, glass-metal, polymer-polymer, and ceramic-ceramic, it has no equivalent for the semiconductor-metal configuration so far, which would be particularly interesting for applications in microelectronics.
CRIS-Team Scopus Importer:2023-04-20